Cyclotomy of order 15 over GF(p2), p=4, 11(mod15) - Christian Friesen; Joseph B. Muskat; Blair K. Spearman; Kenneth S. Williams (International Journal of Mathematics and Mathematical Sciences)
For primes p≡4, 11(mod15) explicit formulae are obtained for the cyclotomic numbers of order 15 over GF(p2).